Electrical demand side contribution to frequency control in power systems: a review on technical aspects. (January 2015) - Dehghanpour, Kaveh; Afsharnia, Saeed
Abstract: Demand side participation in frequency control in power systems, which leads to reduced reliance on conventional thermal units in procuring essential control functions of future energy networks, has gained increased developments in recent years. In this context, the aim of this paper is to provide a review on various design and control schemes of electrical load contribution to frequency control algorithms; both centralized and decentralized control structures are discussed in details. The problem of synchronization of certain types of electrical loads and different proposed methods of avoiding it are also presented and discussed. Synchronization, which is a consequence of collective controllable demand response to system disturbances, might put the power system in jeopardy and cause its failure; therefore, in order to fully comprehend the causes and effects of this phenomenon, an investigation of this event in a power grid with high level of controllable electrical loads is necessary.